Biochemical composition of body compartments during the reproductive cycle of the starfish Allostichaster capensis in Patagonia, Argentina - Rubilar Panasiuk, Cynthia Tamara (2008)
Allostichaster capensis (Perrier, 1875) (= inaequalis) is a fissiparous starfish inhabiting the South Atlantic Ocean coasts. On the Patagonian coast, it displays an annual sexual and asexual reproductive cycle. Fission is most frequent during the austral summer (November-January) and arm regeneration takes place during the rest of the year. In this article, seasonal changes in biochemical composition of body compartments are presented for a population of this fissiparous starfish in Bahia Kaiser, Golfo Nuevo, Chubut, Argentina, from June 2000 to May 2002. During the annual cycle, an inverse relationship between gonad and pyloric caeca indices suggests nutrient transfer. Biochemical analysis revealed that only lipids are translocated from pyloric caeca to gonads at the beginning of gametogenesis.